(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article examines the importance of environmental culture in primary education and explores the benefits of interdisciplinary integration in science teaching. The article also provides practical examples of how interdisciplinary integration can be implemented in the classroom to develop environmental culture in students.